Does Ownership Structure Affect Firm Performance in an Emerging Market? The Case of India - Panda, Brahmadev; Bag, Dinabandhu (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aim: This study aims to examine the impact of ownership structure (ownership concentration and identities) on the financial and market performance of Indian listed firms, post the US financial crisis 2008. Design/Methodology/Approach: This study is based on a six-year financial dataset of 100 Bombay Stock Exchange (BSE) listed firms, from FY 2009-10 to FY 2014-15. The study applies the static panel data model (pooled OLS, fixed effect and random effect) and the dynamic panel data model (two-step generalised method of moments) for the hypotheses testing. Research findings: This study finds that in the case of ownership concentration, large owners have no link with the financial performance. However, they have an adverse impact on the market performance. The presence of promoters, domestic institutions and foreign institutions appears to boost the financial performance, whereas the foreign institutional investment seems to enhance the market performance. Theoretical contribution/Originality: The major contributions of this study are the two dimensions of ownership concentration (large owners) and identity (types of owners) being considered as ownership structure, the use of the dynamic panel models to check for the endogeneity issue and the post US financial crisis analysis derived from this study. All of these contribute to the impact of ownership volatility and performance variation in the context of India, thereby making this study a novel one. Policy implications: Policymakers should consider developing more lucrative policies so as to encourage institutional investors to invest in the Indian market. This is because domestic and foreign institutional owners are central to the enhancement of both the corporate financial and market performance. Further, corporate executives should aim to prevent inefficiencies so as to safeguard the interest of large owners. Research implications/Limitations: This study has used ownership structure as one of the essential governance mechanisms. Future research may consider other mechanisms like board structure or CEO duality. Keywords: Ownership Structure, Performance, Panel Data, GMM, Emerging Market JEL Classification: G32, L25, C33